2021
DOI: 10.1097/corr.0000000000001772
|View full text |Cite
|
Sign up to set email alerts
|

The Charlson and Elixhauser Scores Outperform the American Society of Anesthesiologists Score in Assessing 1-year Mortality Risk After Hip Fracture Surgery

Abstract: Background Risk adjustment has implications across orthopaedics, including informing clinical care, improving payment models, and enabling observational orthopaedic research. Although comorbidity indices (such as the American Society of Anesthesiologists [ASA] classification, Charlson comorbidity index [CCI], and Elixhauser comorbidity index [ECI]) have been examined extensively in the immediate perioperative period, there is a dearth of data on their three-way comparative effectiveness and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…According to the present multivariable Cox proportional hazards regression model, the CCI, but not the ASA score, was an independent factor associated with mortality. This is consistent with Varady et al [7] , which reported that CCI performed better than the ASA score for evaluating the 1-year mortality risk after hip fracture surgery, though some other studies have disagreed. Quach et al [13] found that the ASA score, rather than either version of the CCI, was independently associated with 12-month mortality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the present multivariable Cox proportional hazards regression model, the CCI, but not the ASA score, was an independent factor associated with mortality. This is consistent with Varady et al [7] , which reported that CCI performed better than the ASA score for evaluating the 1-year mortality risk after hip fracture surgery, though some other studies have disagreed. Quach et al [13] found that the ASA score, rather than either version of the CCI, was independently associated with 12-month mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, as a single factor to predict the mortality risk of patients with hip fracture, the CCI did not perform well. Varady et al [7] reported an AUC value of 0.769 (95% CI 0.739-0.800) for CCI for predicting the 1year mortality risk. Karres et al [6] .…”
Section: Discussionmentioning
confidence: 99%
“…The included patients were neck of femur fractures only, and we studied on fracture-related complications but not perioperative complications as current literature has shown that this risk is low with hip screws fixation 6 . Furthermore, studies have shown that the modified Elixhauser’s Comorbidity Measure achieves a very good prediction of complications following hip fractures and have been found to be superior to the Charlson Comorbidity Index 51 , although some studies have shown similar accuracies in terms of mortality risk 52 . We adopted ACCI as it has been published in numerous studies that the score correlates with mortality, complications, and readmission rates after treatment of hip fractures 22 , 33 , 53 55 , and has been used and published in our locality 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Both aCCI and ASA classification are common tools for operative risk stratification. Previous studies have attempted to use CCI and ASA for risk stratification and suggested that CCI performed better than ASA classification in the prediction for 1-year mortality after surgery for hip fractures ( 17 , 18 ). However, some studies suggested that ASA classification was an independent risk factor for it, rather than CCI ( 19 ).…”
Section: Discussionmentioning
confidence: 99%